1992
DOI: 10.1002/jobm.3620320302
|View full text |Cite
|
Sign up to set email alerts
|

Application of newly synthesized detergents in the side chain degradation of plant sterols by Mycobacterium fortuitum

Abstract: Newly synthesized detergents of polyoxyethylene polyoxypropylene co-polymers (Co-EOPO), polyoxyethylene polyoxypropylene adducts of the diethylene triamine (DETA-EOPO), and steroidal detergents (SDD) stimulate significantly side chain degradation of plant sterols referring to both the sterol degradation and the formation of the product, 9 alpha-hydroxy-androsta-4-ene-3,17-dione (9 OH-AD), by Mycobacterium fortuitum NRRL-B-8119. Highest stimulative effects were observed with derivatives of the DETA-EOPO group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Triton X-100 decreased the phenanthrene degradation by a mixed culture (19) and completely inhibited the sterol transformation by Mycobacterium fortuitum (3). Thus, the more hydrophobic surfactants that seem to exhibit better solubilizing properties (3,17) are tolerated by only a few bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triton X-100 decreased the phenanthrene degradation by a mixed culture (19) and completely inhibited the sterol transformation by Mycobacterium fortuitum (3). Thus, the more hydrophobic surfactants that seem to exhibit better solubilizing properties (3,17) are tolerated by only a few bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of surfactants to increase the concentration of hydrophobic compounds in the water phase suggested that the degradation of hydrocarbons might be accelerated by the addition of surfactant. Attempts to enhance the metabolization rates of nonpolar substrates by the use of surfactants gave contradictory results (3,6,8,14,15). Although surfactants have been studied in complex watersoil systems (2,19,23), the effects are not well understood.…”
mentioning
confidence: 99%
“…The mixed culture of soil microorganisms [11] is also tolerant to 2,650 mg/l of Triton X-100 in the hydrophobic substrate (Table 2), as well as the PAH-degrading bacteria of contaminated waste soil [8,27,36]. The single organisms: Pseudomonas species, Sphingomonas yanoikuyae [30,31,39], Bacillus subtilis [3], Escherichia coli [27], and Mycobacterium species [31,40] ( Table 3) are more tolerant to Triton X-100 in hydrophilic substrates than in hydrophobic substrates. Furthermore, the types of hydrophobic substrates affect the tolerance of microorganism to Triton X-100.…”
Section: Inhibitionmentioning
confidence: 99%
“…[52,53]. For instance, cholesterol degradation entails distinct processes, including nucleus cleavage and β-oxidation of the C17 side chain [54][55][56][57]. These pathways operate independently for efficient degradation.…”
Section: Analysis and Reconstruction Of Steroids' Metabolic Pathwaysmentioning
confidence: 99%